EFFECT OF GREEN SYNTHESIZED SILVER NANOPARTICLES ON CARNOSIC ACID CONTENT AND PHYSIO-BIOCHEMICAL PROPERTIES OF ROSMARINUS OFFICINALIS L. - Tayebeh AzariNezhadian; Parastoo Ranjbar; Mahyar Gerami; Moazzameh Ramezani (Journal of the Chilean Chemical Society, 2021)
In biosynthesis of metal nanoparticles, it is possible to replace the old chemical synthesis methods with new environment-friendly procedures. In this study, AgNP was synthesized using extracts of Rosmarinus officinalis L. leaves, and then its effect on biochemical characters, antioxidant enzymes activity, and finally carnosic acid content was studied with its various concentrations. UV–visible spectroscopy was utilized to identify the formation of synthesized AgNP. Synthesized AgNP was confirmed the absorption maxima at 500 nm wavelength. Synthesized AgNP were measured using SEM and showed 21 nm at size and spherical shape. Application of various concentrations of synthesized AgNP demonstrated the concentration dependency so that, in concentration of 40 and 60 mM of synthesized AgNP, dry and fresh weight increased. Application of synthesized AgNP at 40 mM resulted in increase of chlorophyll amount which caused more activity in anti-oxidant enzymes and also biomass accumulation such as soluble carbohydrate and flavonoid. After treatment of synthesized AgNP at 40 mM concentration, HPLC demonstrated an increase in carnosic acid. Here, small nanoparticles revealed increased in secondary metabolites. Synthesized nanoparticles can also be utilized in order to produce natural products and plants with faster growth rates.